The increasing demand for TOEFL tutoring among graduate students: Understanding the motivations behind it - Izzuddin Izzuddin; Budyi Suswanto; Imam Bahrudin (Technium Social Sciences Journal, 2023)
Private extra academic support, also referred to as shadow education has experienced growth, in Asian nations, such as Indonesia. However, despite its use this type of education often receives attention from the government compared to formal schooling. This research aims to explore the motivations that influence university students’ choices to seek academic support specifically for TOEFL preparation—a vital step towards achieving an internationally recognized English proficiency score. Involving 60 university students for the data collection using questionnaire, this study identified factors that drive the demand for private TOEFL tutoring among Indonesian graduate students. Despite concerns about the absence of standardization and potential student exhaustion resulting from tutoring it continues to provide personalized instruction and assistance. This study highlights the role that private supplementary tutoring plays in meeting the growing demand for success and its impact on students’ academic and career paths, in Indonesia.